Chiral self-sorting of (2+3) salicylimine cage compounds - Beaudoin, Daniel; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2017)
An inherently chiral C3-symmetric triaminotribenzotriquinacene was condensed in racemic and enantiomerically pure form with a bis(salicylaldehyde) to form [2+3] salicylimine cage compounds. Investigations on the chiral self-sorting revealed that while entropy favors narcissistic self-sorting in solution, selective social self-sorting can be achieved by exploiting the difference in solubility between the homochiral and heterochiral cages. Gas sorption measurements further showed that seemingly small structural differences can have a significant impact on the surface area of microporous covalent cage compounds.
First published: 22 December 2016
Gesehen am 13.09.2018